The efficiency of cardiac rehabilitation after percutaneous coronary angioplasty - Kocik, Bożena; Spannbauer, Anna; Mika, Piotr (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2019)
Rehabilitation is a multidirectional and comprehensive process of action aimed at facilitating the course of recovery, and improving physical and mental fitness. Advances in recent years related to the development of invasive cardiology and cardiosurgery have contributed to the apparent recovery of cardiac patients, because vascular interventions cannot protect patients from progressive disease, i.e. atherosclerosis. In the case of people with cardiovascular disease, we are talking about comprehensive cardiac rehabilitation aimed at stopping the progression of the disease and preventing its tragic effects. Cardiac rehabilitation and secondary prevention are an integral strategy for the management of percutaneous coronary angioplasty based on the reduction of future morbidity and mortality, as well as further improvement in symptoms. The key role here is played by the modification of atherosclerosis risk factors and the introduction of permanent lifestyle changes related to the particular focus on increasing physical activity.